Book review: Elias, J. and Roberts, J. 2018: Handbook on the International Political Economy of Gender. (April 2019) - Solomon, Divya
Elias, J. and Roberts, J. 2018: Handbook on the International Political Economy of Gender . Cheltenham: Edward Elgar. 544 pp. £162 (Hardcover). ISBN: 9781783478835.